Women’s Ministries in the Framework of National Women’s Machinery: a Study of Reformative Bureaucracy - Mariana Amiruddin (Jurnal Perempuan, 2014)
Indonesia urgently needs national women’s machinery, like ministry of women and commission for women. Beijing Platform for Action had been adopted by the fourth conferenc of women in September 1995 giving specific attention to national women’s machinery in implementing gender mainstreaming at all levels in national development. This machine coordinates and supports all policies regarding strategic decisions and real actions. In July 2004 ECOSOC adopt resolution on national women’s machinery as key actor in bureaucracy reformation. The resolution recommends that national women’s machinery is being put at the highest level to invest authority and equal power to fullfill the mandates.